2022
DOI: 10.1007/s40123-022-00538-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Cyclo Plasty After Failed Glaucoma Surgery: Outcomes and Complications

Abstract: Introduction:The purpose of this study is to report the outcomes and complications of ultrasound cyclo plasty (UCP) after failed glaucoma surgery. Methods: A retrospective case series included patients with previously failed glaucoma surgery who underwent UCP at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Furthermore, whether the thermal effect of HIFU could cause cataracts in eyes with biometric features such as PACG is unknown. Five eyes developed prolonged or rebound anterior chamber inflammation (8.1%), which is lower than in our previous report 25. A wide difference exists in the literature in the incidence of anterior chamber inflammation after UCP because of the differences in sonification exposure time, the number of sectors treated, the heterogenicity of cases, and the history of prior glaucoma surgery.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, whether the thermal effect of HIFU could cause cataracts in eyes with biometric features such as PACG is unknown. Five eyes developed prolonged or rebound anterior chamber inflammation (8.1%), which is lower than in our previous report 25. A wide difference exists in the literature in the incidence of anterior chamber inflammation after UCP because of the differences in sonification exposure time, the number of sectors treated, the heterogenicity of cases, and the history of prior glaucoma surgery.…”
Section: Discussioncontrasting
confidence: 63%
“…Five eyes developed prolonged or rebound anterior chamber inflammation (8.1%), which is lower than in our previous report. 25 A wide difference exists in the literature in the incidence of anterior chamber inflammation after UCP because of the differences in sonification exposure time, the number of sectors treated, the heterogenicity of cases, and the history of prior glaucoma surgery. Two eyes (3.2%) developed transient hypotony with choroidal detachment after UCP, which resolved after the application of cycloplegic agents.…”
Section: Discussionmentioning
confidence: 99%
“…It does not require incisions, has a fast recovery, and allows for quick subsequent anti-VEGF or PRP treatment. The procedure is simple and the treatment time is short, only a few minutes, which improves the efficiency of clinical treatment [13][14][15]25,28] . The results of this study showed that the IOP of both groups of patients with NVG significantly decreased at each postoperative time point compared to preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has the characteristics of short treatment time without surgery and light postoperative reaction, and can be widely used in most types of glaucoma or patients with glaucoma surgery failure, with good IOP reduction effect. It avoids the damage to the eyes caused by continuous high IOP, and enables the condition of glaucoma patients to be controlled in a timely manner [12][13][14][15][16] . However, there are few comparative studies on the clinical efficacy of UCP and Ahmed glaucoma drainage valve (ADV) implantation in the treatment of NVG associated with retinal diseases.…”
Section: Introductionmentioning
confidence: 99%